Optimization of Extraction Parameters by Using Response Surface Methodology, Purification, and Identification of Anthocyanin Pigments in Melastoma malabathricum Fruit. (23rd September 2013) - Anuar, Nordiyanah; Mohd Adnan, Ahmad Faris; Saat, Naziz; Aziz, Norkasmani; Mat Taha, Rosna
Abstract : Anthocyanins not just have various benefits in food industry but also have been used as natural colourants in cosmetic, coating products and as potential natural photosensitizers in solar cell. Thus, the main purpose of this study was to obtain information on the maximum yield of anthocyanin that can be recovered from Melastoma malabathricum fruit. Factors such as extraction temperature, extraction time, and solid to liquid ratio were identified to be significantly affecting anthocyanin extraction efficiency. By using three-level three-factor Box-Behnken design, the optimized conditions for anthocyanin extraction by acidified methanol (R 2 = 0.972 ) were temperature of 60°C, time of 86.82 min, and 0.5 : 35 (g/mL) solid to liquid ratio while the optimum extraction conditions by acidified ethanol (R 2 = 0.954 ) were temperature of 60°C, time of 120 min, and 0.5 : 23.06 (g/mL) solid to liquid ratio. The crude anthocyanin extract was further purified by using Amberlite XAD-7 and Sephadex LH-20 column chromatography. Identification of anthocyanins revealed the presence of cyanidin dihexoside, cyanidin hexoside, and delphinidin hexoside as the main anthocyanins in M. malabathricum fruit.